Aspiring to more? New evidence on the effect of light-touch aspirations interventions in rural Ethiopia - Leight, Jessica; Gilligan, Daniel O.; Mulford, Michael; Taffesse, Alemayehu Seyoum; Tambet, Heleene (Informa UK Limited, 2024)
A growing literature in economics has analysed the effects of psychological interventions designed to boost individual aspirations as a strategy to increase households’ propensity to make long-term investments and thus reduce poverty. This paper reports on a randomised controlled trial evaluating a short video-based intervention designed to increase aspirations of adults in poor rural Ethiopian households who are beneficiaries of the Productive Safety Net Program, the main government safety net program in Ethiopia. Evidence from a sample of 5,258 adults from 3,220 households is consistent with the hypothesis that there are no significant effects of the intervention on self-reported aspirations for the household, educational investment in children, or savings nine months post-treatment. This suggests that the effect of light-touch aspirations treatments for extremely poor adults may be limited in this context.